"I don't care anymore if she wants to cry through the whole conversation, because it needs to be addressed": Adult siblings' experiences of the dynamics of future care planning for brothers and sisters with a developmental disability. Issue 5 (25th February 2020) - Leane, Máire
Abstract: Background: In families with a member with a developmental disability (DD), future care planning is limited (Brennan et al., Journal of Applied Research in Intellectual Disabilities, 31, 2018, 226; Bowey and McGlaughlin, British Journal of Social Work, 31, 2007, 39; Davys et al., Journal of Intellectual Disability, 14, 2010, 167; Davys et al., British Journal of Learning Disabilities, 43, 2014, 219; Davys et al., Journal of Applied Research in Intellectual Disabilities, 29, 2016, 220). However, most siblings without disabilities (SWD) expect to be involved in the future care of their brother or sister with DD (Benderix and Sivberg, International Paediatric Nursing, 22, 2007, 410; Gomez de la Cuesta and Cos, We exist too: Valuing the contributions of siblings, UK, National Autistic Society, 2012; Heller and Arnold, Journal of Policy and Practice in Intellectual Disabilities, 7, 2010, 16). Materials and Methods: Based on qualitative interviews with 25 SWD in Ireland, this article explores how SWD experience future planning. Results and Discussion: The findings indicate that SWD experience care planning as an ongoing, fluid and emotionally charged process. Parental fears, about future care landscapes they do not control and about passing on intergenerational care responsibilities, emerge as key factors inhibiting planning. Conclusion: Attention to the highly emotive nature of care concerns, and to the tentative pace of planning that is comfortable for families, will help professionals provide optimum planning support.